LKJ Data Preparation Technology and Application Research Based on Train Diagram Data - LEI Liping; YANG Shaobin; ZHU Chengjian; DENG Yong (Kongzhi Yu Xinxi Jishu, 2022)
In view of the problems such as large works of manual preparation of LKJ basic source data and excessive dependence on personal ability of data compilers, this paper proposes a LKJ data preparation technology based on technical data of train diagram, and a set of LKJ data preparation system is developed based on this technology. The system realizes intelligent identification of technical data of train diagram adopting Excel, and realizes transformation of technical data of train diagram into standard engineering data, then converts the engineering data into LKJ basic source data. It builds engineering database and realizes LKJ basic data management and preparation. Based on the engineering data of main line annunciator and station annunciator, it realizes automatic preparation of line frame data such as station, track and annunciator zoning, and realizes automatic preparation of display data such as slope, bend, bridge and tunnel according to the starting and ending mileage and line information of zoning. In order to facilitate the upgrading of LKJ basic source data, the system realizes the comparison and automatic update between LKJ basic source data and engineering data. The field test shows that it can realize automatic production of nearly 90% LKJ basic source data by this technology, which can effectively improve the production efficiency of data and reduce the intensity of data preparation.